USULAN PENINGKATAN KUALITAS PULP DENGAN MENGGUNAKAN METODE SEVEN TOOLS DAN NEW SEVEN TOOLS DI PT. IK - Vera Devani; Melany Oktaviany (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
PT. IK is a company engaged in the manufacture of pulp and paper. Pulp production produced in each process sometimes does not meet the standard specifications of the quality set. The method used to solve the problem is the seven tools and the new seven tools. The research objectives were to determine priorities based on the type of defect, identify the cause of quality deviations, and determine the action to be taken to improve pulp quality. Priority repair on defects in the Blow Line Kappa Number, Ex Metso Press Soda Loss as Na2SO4, Post MCO2 Outlet Single Diffuser Residual Soda, and Ex Khamyr Press Soda Loss as Na2SO4. The causes of quality deviations include the lack of operator understanding of the SOP, the stages of the production process lacking supervision, the selection of raw materials that do not meet specifications, poor machine conditions, operator error or human error, and inappropriate chemical levels. Actions taken to improve the quality of the pulp are by conducting employee training, checking machines, continuously monitoring and controlling the production process, using work methods that are under with the SOP set by the company, environmental conditions that are under occupational safety and health, and optimizing operator performance.